(untitled) (International Journal of Engineering and Computer Science, 2017)
In this paper, we investigate some properties of the approximations determined by a class of equivalence relations, in Pawlak’s single granulation point of view. A comparison of these approximations with the optimistic and the pessimistic multi-granular approximations is also presented. It has been observed that the accuracy measure and the precision of these approximations are greater than those of the two multi-granular approximations. The topology determined by them is found to be stronger than the topology determined by the pessimistic multi-granular approximations. Finally the results are verified through an example in the context of an information system.